2002
DOI: 10.1046/j.1365-2842.2003.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral disease among the institutionalized and non‐institutionalized elderly in Hong Kong

Abstract: The study aimed to describe and compare the psychosocial and functional impact of oral disease on the quality of life of the institutionalized and non-institutionalized elderly in Hong Kong. A total of 268 institutionalized and 318 non-institutionalized elderly aged 60-80 years took part. The 49-statement Oral Health Impact Profile (OHIP) was administered in a structured interview format and sociodemographic information collected prior to a clinical, oral examination. A greater number of the institutionalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 21 publications
3
62
0
5
Order By: Relevance
“…Thus, our data must be interpreted with caution as they relate only to self-selecting community-dwelling older adults. Inclusion of those who are institutionalized would have had the greatest impact on the root caries experience as the prevalence of dental disease is very high in this group [20][21][22]. It is also reported that persons with a less favourable attitude to oral care are probably less inclined to participate in an epidemiologic study [23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our data must be interpreted with caution as they relate only to self-selecting community-dwelling older adults. Inclusion of those who are institutionalized would have had the greatest impact on the root caries experience as the prevalence of dental disease is very high in this group [20][21][22]. It is also reported that persons with a less favourable attitude to oral care are probably less inclined to participate in an epidemiologic study [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of countries, the prevalence of gingivitis and initial periodontal pockets are the most frequent and to a large extent these reflect poor oral hygiene. The inter-country variation in prevalence rates of severe periodontitis is high; the mean number of older people affected by severe periodontitis ranges from 5 to 20% although some countries exceed these levels [15]. Among the negative impacts on daily life of poor oral health are reduced chewing performance, constrained food choice, weight loss, impaired communication, low self-esteem and well-being Kandelman et al [16].…”
Section: Diseases Related To the Oral Cavitymentioning
confidence: 99%
“…Previous studies have found that socioeconomic status, dental factors, dental service attendance, selfperceived oral health and psychological factors may affect people's OHRQOL. [13][14][15][16][17][18][19] In addition, several studies amongst patients with OFP seeking dental treatment showed that OHRQOL varied with diagnostic subgroups, pain characteristics and psychological factors. [20][21][22][23] Nevertheless, patients who seek treatment may not fully represent all those living in the community.…”
Section: Introductionmentioning
confidence: 99%